Cryptococcus gattii: Emergence in Western North America: Exploitation of a Novel Ecological Niche - Kausik Datta; Karen H. Bartlett; Kieren A. Marr (Interdisciplinary Perspectives on Infectious Diseases)
The relatively uncommon fungal pathogen Cryptococcus gattii recently emerged as a significant cause of cryptococcal disease in human and animals in the Pacific Northwest of North America. Although genetic studies indicated its possible presence in the Pacific Northwest for more than 30 years, C. gattii as an etiological agent was largely unknown in this region prior to 1999. The recent emergence may have been encouraged by changing conditions of climate or land use and/or host susceptibility, and predictive ecological niche modeling indicates a potentially wider spread. C. gattii can survive wide climatic variations and colonize the environment in tropical, subtropical, temperate, and dry climates. Long-term climate changes, such as the significantly elevated global temperature in the last 100 years, influence patterns of disease among plants and animals and create niche microclimates habitable by emerging pathogens. C. gattii may have exploited such a hitherto unrecognized but clement environment in the Pacific Northwest to provide a wider exposure and risk of infection to human and animal populations.